Antioch, December 13 115 AD: an earthquake, a date and a coin in the appendix (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2021)
Come ricordano Dione Cassio e Malalas, durante la spedizione partica di Traiano un terremoto di ampia dimensione colpì la città di Antiochia e il territorio circostante, causando danni ingenti e un numero non quantificabile di vittime. Anche Traiano, acquartierato in città, a stento poté uscirne illeso grazie all’intervento salvifico di un “essere più grande dell’umano”. Nel presente contributo, l’evento sismico viene analizzato alla luce della difficile congruenza delle fonti antiche e delle ricostruzioni contemporanee, spesso figlie di un’“ansia da accumulo” dalle diverse evidenze archeologiche e (anche) numismatiche. As recalled by Dio Cassius and Malalas, during Trajan’s Parthian expedition a major earthquake occurred in the city of Antioch and in the surrounding area, causing extensive damages and an undetermined number of victims. Even Trajan, quartered in the city, barely managed to escape unharmed thanks to the saving intervention of a “being greater than the human”. In this paper, the Antioch’s earthquake is analysed in the light of the difficult congruence of ancient sources and contemporary reconstructions, which are often the result of an “anxiety of accumulation” of various archaeological and (also) numismatic evidence.
Keywords: Antioch; Trajan; earthquake; archaeoseismology